Attempts to induce melanosome degradation in vivo - Borovanský, J; Hach, P; Smetana, K; Elleder, M; Matous-Malbohan, I (Folia biologica, 1999)
Contradiction between repeatedly reported electron microscopic and histochemical observation of melanosome disintegration in the presence of lysosomal enzymes in vivo and failing attempts to induce such degradation by biochemical means in vitro with the aim to explain chemical mechanism(s) of this process belongs to chronically challenging problems in biochemistry of melanin structures. Attempts have been made to bring about melanosome disintegration in vivo by inoculating melanosomes isolated from dog hair into the tissue of amelanotic Bomirski melanoma and into peritoneal cavities of DBA/2 and C57BL/6J mice, and by repeated injection of melanosomes isolated from Bomirski pigmented melanoma into Syrian hamster foot pads. Both histological and electron microscopic observations demonstrated that melanosomes were phagocytized by macrophages and sporadically by fibroblasts. In peritoneal cavities the injected foreign melanosomes remained mostly extracellularly, were surrounded by foreign body multinuclear cells and formed granulomas. There were no convincing signs of degradation of the hair melanosomes, which behaved like inert foreign bodies. Only some phagocytized Bomirski hamster melanoma melanosomes tended to lose their integrity. Our data suggest that melanosomes devoid of their limiting membranes are not necessarily prone to extensive disintegration in vivo. The earlier reported association of lysosomal enzymes with disintegrating melanosomes does not constitute an evidence for their participation in melanosome degradation. Considering the structure of melanins, redox mechanisms (analogous with the metabolism of polycyclic hydrocarbons (DePierre and Ernster, 1978)) seem to be more probably involved in pigment degradation than hydrolytic reactions.
Keywords: Granuloma; psi; Foreign-Body Reaction; křečci praví; Lysosomes; Dogs; vlasy, chlupy; melaniny; Peritoneal Cavity; makrofágy; noha (od hlezna dolů); zvířata; peritoneální dutina; myši; Mice, Inbred DBA; myši inbrední C57BL; melanozomy; křeček rodu Mesocricetus; Mice; Hair; fagocytóza; Mesocricetus; Melanosomes; Melanins; reakce na cizí těleso; myši inbrední DBA; granulom; Mice, Inbred C57BL; Cricetinae; Foot; lyzozomy; fibroblasty; Animals; Macrophages; Melanoma, Experimental; melanom experimentální; Phagocytosis; Fibroblasts